Autour de la retraduction: Sur l'exemple des traductions françaises de Pan Tadeusz - Skibińska, Elżbieta (Verbum – Analecta Neolatina, 2006)
The phenomenon of retranslation may be accounted for in a number of ways. Some of the commonly mentioned factors are: the ageing of the existing translation(s), the necessity to introduce corrections or improvements, and commercial reasons, too. Some case studies show that other factors can lead to retranslation, namely those resulting from the needs of the target culture. The present paper offers yet another possible explantion. The case of several French renditions of the Polish national epic Pan Tadeusz (1834) by Adam Mickiewicz, shows that the needs of the original culture can also motivate retranslation.